2017
DOI: 10.1074/jbc.m116.764910
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1/Smad3 Pathway Targets PP2A-AMPK-FoxO1 Signaling to Regulate Hepatic Gluconeogenesis

Abstract: Edited by Jeffrey E. PessinMaintenance of glucose homeostasis is essential for normal physiology. Deviation from normal glucose levels, in either direction, increases susceptibility to serious medical complications such as hypoglycemia and diabetes. Maintenance of glucose homeostasis is achieved via functional interactions among various organs: liver, skeletal muscle, adipose tissue, brain, and the endocrine pancreas. The liver is the primary site of endogenous glucose production, especially during states of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 43 publications
4
69
0
Order By: Relevance
“…5A, B). The activation of AMPK has been proclaimed to repress FoxO1-mediated hepatic gluconeogenesis (25). Consistently, we found that the phosphorylation of AMPK-a and ACC was significantly reduced in CSE 2/2 mice.…”
Section: Repression Of Insulin and Ampk Signaling Pathways By Cse Defsupporting
confidence: 85%
“…5A, B). The activation of AMPK has been proclaimed to repress FoxO1-mediated hepatic gluconeogenesis (25). Consistently, we found that the phosphorylation of AMPK-a and ACC was significantly reduced in CSE 2/2 mice.…”
Section: Repression Of Insulin and Ampk Signaling Pathways By Cse Defsupporting
confidence: 85%
“…Recent studies support the notion that FoxO family members act synergistically with the TGF-b1 signaling pathway to promote gene expression of many targets in fibroblasts (21)(22)(23). Subsequent in vitro studies were therefore performed to study the effects of PFD treatment on the TGF-b1 signaling pathway in iPAH PA-SMCs.…”
Section: Pfd Increases Foxo1 Expression and Nuclear Localization In Imentioning
confidence: 94%
“…PP2A is frequently inactivated in human cancers as a means to removing its tumor suppressive activity, thereby allowing for unregulated growth that is a hallmark of malignancy. While cancer remains the most researched disease context for PP2A disruption, PP2A inhibition also contributes to pathogenesis in cardiovascular disease [1-3], diabetes [4-7], neurodegenerative disease (e.g. Alzheimer’s and Parkinson’s disease) [8-12] and developmental conditions involving intellectual disability [13, 14].…”
Section: Introductionmentioning
confidence: 99%